2021
DOI: 10.1038/s41598-020-79362-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analyses identifies new domains and structural differences among Streptococcus pneumoniae immune evasion proteins PspC and Hic

Abstract: The PspC and Hic proteins of Streptococcuspneumoniae are some of the most variable microbial immune evasion proteins identified to date. Due to structural similarities and conserved binding profiles, it was assumed for a long time that these pneumococcal surface proteins represent a protein family comprised of eleven subgroups. Recently, however, the evaluation of more proteins revealed a greater diversity of individual proteins. In contrast to previous assumptions a pattern evaluation of six PspC and five Hic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Importantly, the knowledge of dynamical binding nature of RBD with ACE2 is also essential to identify the drug targets for the variants which has mutations, this often alter the binding mode of virus and entry mechanism to the host cells. Several reports outline the evidence of conformational change of binding domain that occurs due to the mutations in SARS‐CoV‐2 variants; these previous studies which demonstrate the same with their experimental and computational reports 16–20 . Protein structure of RBD bound with ACE2 have been reported (PDB code: 6M0J) and the binding nature also revealed by J Lan et al which states that the sequence of this protein is highly similar to the SARS‐CoV RBD and has improved binding nature 6 .…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Importantly, the knowledge of dynamical binding nature of RBD with ACE2 is also essential to identify the drug targets for the variants which has mutations, this often alter the binding mode of virus and entry mechanism to the host cells. Several reports outline the evidence of conformational change of binding domain that occurs due to the mutations in SARS‐CoV‐2 variants; these previous studies which demonstrate the same with their experimental and computational reports 16–20 . Protein structure of RBD bound with ACE2 have been reported (PDB code: 6M0J) and the binding nature also revealed by J Lan et al which states that the sequence of this protein is highly similar to the SARS‐CoV RBD and has improved binding nature 6 .…”
Section: Introductionmentioning
confidence: 59%
“…Several reports outline the evidence of conformational change of binding domain that occurs due to the mutations in SARS-CoV-2 variants; these previous studies which demonstrate the same with their experimental and computational reports. [16][17][18][19][20] Protein structure of RBD bound with ACE2 have been reported (PDB code: 6M0J) and the binding nature also revealed by J Lan et al which states that the sequence of this protein is highly similar to the SARS-CoV RBD and has improved binding nature. 6 P Han et al reported an insights into RBD-ACE2 binding for emerging SARS-CoV-2 variants which characterize the binding using cytometry.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…HUS A strain showed higher H2O2 excretion (~2-fold more than WT) than the other strains assayed. Previously, we showed that HUS A strongly binds lactoferrin (30,31). Thus, the HUS A strain (from now on referred to as the Sp-HUS strain), which was isolated from a 2-year-old patient suffering from HUS, was chosen as the focus for the rest of this study.…”
Section: Sp-hus Strain Shows Cytotoxicity Towards Human Red Blood And...mentioning
confidence: 99%
“…PspA and PspC share structural similarities: each has modular, unique, and variable N-terminal regions, a proline-rich domain that varies in size and almost identical C-terminal regions ( 27 , 28 ) ( Fig. S1 ).…”
Section: Introductionmentioning
confidence: 99%